Gauge preservation in renormalization for Yang–Mills and gravity theories - Santillán, Osvaldo Pablo (2025)
In the present work, multiplicative renormalization procedure for Yang-Mills theories is reviewed. While this subject is not new, it is suggested that a clear understanding of these methods leads to a systematic way for interpreting the counter terms needed for non multiplicative renormalization (Dixon and Taylor in Nucl Phys B 78:552, 1974) of quantum gravity, for models such as well known Stelle Model. Some of these models are renormalizable, however they contain apparent instabilities leading to possible unitarity loss. The systematic procedure discussed along the text may be interesting, especially in the modern context, since there are efforts for avoiding with those apparent instabilities by employing variants of the standard quantization methods.